Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome in two young children: the importance of an early diagnosis - Massimo Luca Castellazzi; Susanna Esposito; Laura Elisabetta Claut; Valeria Daccò; Carla Colombo (BMC, 2018)
Abstract Background Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a serious life-treating condition characterized by skin eruption, fever, haematologic abnormalities, and multi-organ involvement that can be fatal if unrecognized, especially in patients with liver failure. Diagnosis may be difficult because it is rarely described in children and can mimic many different conditions. Case presentation We report two cases of DRESS syndrome due to prolonged antibiotic treatment in young children in whom recovery occurred following different therapeutic approaches. A previously healthy 5-year-old boy had been receiving intravenous vancomycin for right wrist and left elbow osteomyelitis and developed DRESS syndrome on day 30. The patient achieved a complete resolution of all symptoms with pulse methylprednisolone followed by oral prednisone. A 4-year-old girl with cystic fibrosis, pancreatic insufficiency, chronic pulmonary colonization by Gram-positive bacteria admitted for pulmonary exacerbation was treated with intravenous piperacillin-tazobactam and tobramycin. After 14 days of treatment, she developed DRESS syndrome: antibiotic treatment was therefore stopped, and without any further therapy, a progressive resolution of the patient's clinical features was observed within 7 days, while the normalization of laboratory abnormalities was achieved at 14 days. Conclusions Our cases highlight that paediatricians should be aware of the clinical presentations of and therapeutic approaches for DRESS syndrome, especially in children receiving long-term antibiotic treatment. The removal of the offending drug is crucial and may be the only life-saving measure. In more aggressive cases, corticosteroid or other immunosuppressive drugs should be considered to achieve the best outcome.